2002
DOI: 10.1128/jcm.40.2.704-706.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses to the Mycobacterium tuberculosis -Specific Antigen ESAT-6 Signal Subclinical Infection among Contacts of Tuberculosis Patients

Abstract: Diagnosis of latentMycobacterium tuberculosis infection is considered essential for tuberculosis control but is hampered by the lack of specific reagents. We report that strong recognition of tuberculosis complex-specific antigen ESAT-6 by healthy household contacts of tuberculosis patients correlates with the subsequent development of active tuberculosis during a 2-year follow-up period.In the next year tuberculosis (TB) is expected to be responsible for more than 2 million deaths and up to 8 million new infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
146
1
9

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 233 publications
(168 citation statements)
references
References 13 publications
12
146
1
9
Order By: Relevance
“…The antigen possesses various specific T-cell epitopes that induce a cellular response and lead to increased interferon γ production in patients with subclinical or active tuberculosis but not in unexposed healthy individuals (13). This cell-mediated response has also been associated with increased risk of disease (30). A recent study showed that the humoral response to ESAT-6 may be associated with inactive tuberculosis but not with active tuberculosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…The antigen possesses various specific T-cell epitopes that induce a cellular response and lead to increased interferon γ production in patients with subclinical or active tuberculosis but not in unexposed healthy individuals (13). This cell-mediated response has also been associated with increased risk of disease (30). A recent study showed that the humoral response to ESAT-6 may be associated with inactive tuberculosis but not with active tuberculosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…These data provide the first clear indication of why this may occur. It has an important implication for human TB as well: deviation of the immune response into an unproductive pathway may explain why infected individuals can progress to clinical TB even though they make a strong IFN-c response against M. tuberculosis antigens [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Others recommend that IGRAs completely replace the tuberculin skin test for identifying latent infection [85]. Today, some data from prospective studies are now emerging that look at the risk of tuberculosis in those with a positive IGRA [86,88,121,122].…”
Section: Section 4 Contact Tracing For Latent Tuberculosis Infectionmentioning
confidence: 99%